Water availability and its use in agriculture - Molden, David J.; Vithanage, Meththika; Fraiture, Charlotte de; Faures, J.M.; Gordon, L.; Molle, Francois; Peden, Donald G. (Elsevier, 2011)
Water scarcity is a reality in the world today, and is a major threat to our food production systems that have to provide enough food for a growing and wealthier population. Managing water for agriculture is a major part of the solution for scarcity. This chapter provides information on water availability and its use in agriculture now and in the future. Detail is provided on rainfed, irrigated, fish and livestock systems, the governance of water in river basins, and environmental and health implications.